Pengaruh Intellectual Capital Terhadap Kinerja Perusahaan High Intensive IC - Sintatul Maulidia; Susi Handayani (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2021)
This study empirically examines whether each component of intellectual capital has an effect on the performance of companies in the high intensive IC category in Indonesia. Measurement of company performance uses ROA and ATO, while intellectual capital uses MVAIC. The sample used was 154 companies in the high intensive IC category listed on the IDX from 2015 to 2019. Multiple linear regression analysis was used in data testing with the SPSS program. The test results obtained are that structural capital, relational capital, capital employed have a positive effect on the performance of high intensive IC category companies on the IDX for the 2015 - 2019 period. However, human capital shows a negative effect on the performance of high intensive IC category companies on the IDX period. 2015 - 2019.